2019
DOI: 10.1021/acs.orglett.9b00773
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Methyl Carbonate as an Effective C1 Synthon. Synthesis of Carboxylic Acids, Benzophenones, and Unsymmetrical Ketones

Abstract: Reported is the synthesis of carboxylic acids, symmetrical ketones, and unsymmetrical ketones with selectivity achieved by exploiting the differential reactivity of sodium methyl carbonate with Grignard and organolithium reagents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 17 publications
(13 reference statements)
1
21
0
Order By: Relevance
“…As expected, when these conditions were employed, the yield of the desired tertiary alcohol 3 b decreased considerably and ketone 2 b appeared as by-product (Table 1, entry 17). A similar scenario was observed when MeLi was used as alkylating reagent (entries [18][19], obtaining better results when 2-MeTHF was employed as solvent. Finally, when 5 equivalents of the aromatic lithium reagent PhLi were employed, either in 2-MeTHF or in the absence of external solvents, none of the expected products were observed but the corresponding homo-coupling product PhÀ Ph.…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…As expected, when these conditions were employed, the yield of the desired tertiary alcohol 3 b decreased considerably and ketone 2 b appeared as by-product (Table 1, entry 17). A similar scenario was observed when MeLi was used as alkylating reagent (entries [18][19], obtaining better results when 2-MeTHF was employed as solvent. Finally, when 5 equivalents of the aromatic lithium reagent PhLi were employed, either in 2-MeTHF or in the absence of external solvents, none of the expected products were observed but the corresponding homo-coupling product PhÀ Ph.…”
Section: Resultssupporting
confidence: 69%
“…Interestingly, it is important to note that under our experimental conditions, we never observed the formation of ketone 2 a as the main product of the reaction, in contrast with the previous studies reported by Jessop and Snieckus, in which sodium methyl carbonate was employed as C1 feedstock. [19] Next, and to expand further the scope of our study, the reactivity of carbonate 1 a with other organolithium reagents (RLi) under the optimized reaction conditions (5 equivalents, ambient temperature, under air) was also investigated by using 2-MeTHF as reaction medium or in the absence of any additional VOC solvent. Astonishing, in the case of EtLi and when 2-MeTHF was used as solvent, a near-quantitative yield of 3 b was observed (90 %), being the unique product of the reaction, as ketone 2 b was not detected (Table 1, entry 16).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The production of benzophenone from carboxylic acid salts using Grignard reagents has been observed recently where the Grignard intermediate product benzoate salt was then reacted with organolithium reagents to form a variety of benzophenones. 21 While the previous report required the organolithium reagent to produce the benzophenone product, this process may occur with Grignards alone at the low yields observed in this study. Correspondingly this would involve the reaction of the magnesium benzoate salt with a second molecule of phenylmagnesium bromide followed by elimination of magnesium oxide.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 62%